1996
DOI: 10.1097/00005392-199603000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Prospective characterization of pathological features of Prostatic Carcinomas Detected Via Serum Prostate Specific Antigen Based Screening

Abstract: We concluded that the pathological features of most prostatic carcinomas detected via PSA based screening do not resemble those of autopsy cancers, and that most prostatic cancers detected in screening programs are likely to be clinically important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 22 publications
5
50
0
Order By: Relevance
“…23 Pattern 3 has been characterized as having three distinctive appearances, designated patterns 3A, 3B, and 3C. It has been suggested that there is increased aggressiveness of pattern 3 carcinoma proceeding from pattern 3A to 3B to 3C, 10 but no data have been published in support of this notion.…”
Section: Gleason Pattern 3 (Grade 3)mentioning
confidence: 99%
See 1 more Smart Citation
“…23 Pattern 3 has been characterized as having three distinctive appearances, designated patterns 3A, 3B, and 3C. It has been suggested that there is increased aggressiveness of pattern 3 carcinoma proceeding from pattern 3A to 3B to 3C, 10 but no data have been published in support of this notion.…”
Section: Gleason Pattern 3 (Grade 3)mentioning
confidence: 99%
“…23,40 These models are not perfect, but can provide an estimate of risk for the patient having a small, organ-confined cancer without a high-grade Gleason pattern in the whole gland.…”
Section: Relationship Of Gleason Grade To Pathologic and Clinical Endmentioning
confidence: 99%
“…With widespread screening, men are diagnosed with CaP at a younger age, exhibit lower stage disease and smaller tumors, and have lower serum PSA, Gleason score 6 or 7, and nonpalpable disease (75%) [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. While a great number of men are still diagnosed with advanced disease and approximately 25% of all CaP patients detected will recur [2,4,12], approximately 25% of men undergoing PSA testing in referral and screened populations will have well differentiated (Gleason score <7), small volume (<0.5 cc) tumors known to demonstrate a long natural history [8,9,15]. The Epstein criteria, PSA density <0.15 ng/ml/g without adverse biopsy pathology (Gleason score <7, <3 cores involved with cancer, and <50% cancer involving any single core), correctly predict small volume, low grade tumors in 73% of men undergoing radical prostatectomy [8].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Humphrey et al (4), 78 of 100 consecutive patients who underwent radical prostatectomy for cancer detected with PSA screening had clinical stage T1c disease.…”
mentioning
confidence: 99%
“…Patients with clinical stage T1c disease who are treated with radical prostatectomy may harbor either clinically nonimportant cancer or cancer that is substantial in size, grade, and extent at surgical-pathologic analysis (4)(5)(6). For example, in a case series of 157 consecutive men who underwent radical prostatectomy for clinical stage T1c prostate cancer, 26% of tumors were considered "insignificant" or "minimal" (no larger than 0.5 cm 3 , confined to the prostate, and Gleason score lower than 7), 37% were moderate (Gleason score lower than 7 and either larger than 0.5 cm 3 or with capsular penetration), and 37% were advanced (capsular penetration, Gleason score higher than or equal to 7 or positive margins, or tumor involvement of seminal vesicles or lymph nodes) (5).…”
mentioning
confidence: 99%